Veterinary technician's manual for small animal emergency and critical care - Norkus, Christopher L. (Hoboken, NJ : Wiley, 2018)
'This book provides an in-depth and cutting-edge, yet easy-to-navigate, reference on emergency and critical care for veterinary paraprofessionals of all skill levels'--Provided by publisher.
Nursing Care of the Renal PatientTraditional Therapies; Advanced Therapies; References; Chapter 10 Endocrine and Metabolic Emergencies; Introduction; Anatomy and Physiology of the Endocrine System; Specific Endocrine Diseases; References; Chapter 11 Hemolymphatic, Immunological, and Oncology Emergencies; Introduction; Physiology of Blood Components; Blood Component Disorders; The Immune System; Immune System and Oncology Disorders; Physiology of Hemostasis; Laboratory Assessment of Hemostasis; Hemostatic Testing Modalities; Hemostatic Disorders; The Lymphatic System; References
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Emergency Treatment -- veterinary; Pets; Veterinary emergencies; TECHNOLOGY & ENGINEERING / Agriculture / Animal Husbandry; Veterinary emergencies; Electronic books